Locking the Taylor Spatial Frame – The effect of three additional longitudinal rods on osteotomy site movements. (December 2022) - Lotzien, Sebastian; Rosteius, Thomas; Jettkant, Birger; Cibura, Charlotte; Rausch, Valentin; Schildhauer, Thomas Armin; Geßmann, Jan
Abstract: Background: In clinical practice, even when the fixator is locked, a noticeable laxity of the construct can be observed. This study was designed to measure the stiffness of the fixator and to analyze the movements of the osteotomy site. Furthermore, the effect of three additional longitudinal rods on the locking of the construct was analyzed. Methods: Five synthetic tibia/fixator models (Model A) were tested under rotational torque (40 Nm) and axial compression (700 N). Three additional rigid rods were subsequently mounted, and the tests were repeated (Model B). The movements of the fixator as well as the osteotomy site were registered by a digital optical measurement system. Load- deformation curves, and so stiffness of the models, were calculated and compared. Findings: Under rotational and axial loadings, Model A was found to be less rigid than Model B ( p = 0.034; p = 0.194). Notably, Model A showed a region of laxity around neutral rotational (ΔF = 5 Nm) and axial (ΔF = 16.64 N) loading before a linear deformation trend was measured. Concomitantly, greater osteotomy site movement was measured for Model A than for Model B under full loading ( p = 0.05) and within the region of increased laxity ( p = 0.042). Interpretation: The fixator showed an element of laxity around neutral axial and rotational loading, which transferred to the bone and led to a notable amount of osteotomy gap movement. Mounting three additional rods increased the stiffness of the construct and therefore reduced the movement of the osteotomy site. Highlights: The Taylor Spatial Frame shows an element of laxity around neutral loading. The laxity leads to a notable amount of osteotomy gap movement. Not only axial, but bending, shear and rotational movements have been measured. Additional longitudinal rods effectively eliminate the instability of the construct.